Laser-driven hole boring and gamma-ray emission in high-density plasmas. (16th February 2015) - Nerush, E N; Kostyukov, I Y
Abstract: Ion acceleration in laser-produced dense plasmas is a key topic of many recent investigations thanks to its potential applications. Indeed, at forthcoming laser intensities ( I ≳ 10 23 W cm −2 ) interaction of laser pulses with plasmas can be accompanied by copious gamma-ray emission. Here we demonstrate the mutual influence of gamma-ray emission and ion acceleration during relativistic hole boring in high-density plasmas with ultra-intense laser pulses. If the gamma-ray emission is abundant, laser pulse reflection and hole-boring velocity are lower and gamma-ray radiation pattern is narrower than in the case of low emission. Conservation of energy and momentum allows one to elucidate the effects of the gamma-ray emission which are more pronounced at higher hole-boring velocities.